Innovative educational program designed for developing transversal skills of prospective teachers (Journal of Educational Sciences, 2023)
Contemporary preparation of pedagogical personnel is characterized by rapid changes and the emergence of new interdisciplinary professional and scientific fields, which makes the mission of higher pedagogical education more uncertain and complex. In this regard, this article presents the issue of possible formation of transversal competencies among students of a professional pedagogical university. The concept of transversal competency is analyzed and its components are defined. Additionally, the development of a competency-oriented educational environment can be considered from the perspective of transversal orientation. In this context, a survey was conducted to identify the initial state of transversal skills among future teachers. The theoretical analysis and empirical research presented in this article resulted in the development of an Innovative educational program “Mentor-teacher of primary education” designed for developing transversal skills of prospective teachers.The conducted study has expanded the understanding of the implementation and development of transversal skills in the preparation of future educators. The results obtained in the process of writing this article will have a positive effect on the preparation of future teachers. The transformation of domestic and foreign advanced experience in the development of transversal skills will serve as a basis for the development of design thinking among future teachers. Additionally, the proposed innovative educational program will serve as a foundation for improving the quality of professional training for future teachers in the university and for effective planning and organization of the educational process by practicing teachers.Key words: transversal competency, transversal skills, 21st-century competencies; adoption of innovation; innovative educational program; teacher perceptions; prospective teachers.